THE RELATIONSHIP BETWEEN VIOLENCE SHOWS ON TELEVISION AND BULLYING BEHAVIORS AMONG STUDENTS - Hernawati, Ade; Ruhimat, Mamat; Sapriya, Sapriya (JURNAL PENDIDIKAN ILMU SOSIAL, 2019)
This research is motivated by the increasing frequency and variety of violence on television. The show was consumed by many people, including junior high school students. The problem that arises is that many junior high school students are watching. The purpose of this study is to describe the shows of violence on television and bullying behavior among students in schools, and analyze the relationship of television violence to students' bullying behavior in schools. The research subjects were students of Majalengka 6 Middle School. Based on the hypothesis and the type of data used, testing will use a nonparametric statistical test. The reason for using this statistical test is because the data taken is in the form of nominal and ordinal data. The analysis uses the Spearman rank correlation test. The results of the study show that the description of violent shows on television, bullying behavior is included in the low category. There is a significant relationship between the display of violence on television and the bullying behavior of students at school.Â